DINAMIKA KEPRIBADIAN TOKOH DALAM NOVEL HARAPAN DI ATAS SAJADAH KARYA MAWAR MALAKA - Rahmatia Nasaru; Moh. Karmin Baruadi; Ellyana Hinta (Jurnal Bahasa, Sastra, dan Budaya, 2021)
This study aims to describe the personality dynamics of the characters in the novel Harapan Di Atas Sajadah by Mawar Malka. The theory used is Jungian psychology, namely the theory of the importance of consciousness and the unconscious to form a complete person in relation to experiences and relationships with the Creator. The research method used a qualitative descriptive method. The research data is in the form of quotes through dialogue between characters and stories that describe the dynamics of personality in terms of the principles of interaction, function, and purpose of using psychic energy. The results of the research and discussion show that (1) the dynamics of personality in terms of the principles of interaction consist of the principles of opposition, compensation, and merger. This principle becomes the basis for the dynamics of personality that initially has a bad personality to become better, (2) personality dynamics in terms of the function of using psychic energy, namely the strength of enthusiasm, desire, and will, (3) personality dynamics in terms of the purpose of using psychic energy consisting of progressions and regressions. The personal progression of a character displays two types of personality, namely an extroverted attitude (open) and an introverted attitude (closed). Thus, the dynamics of the character's personality show significant changes. Changes related to social problems and their relationship with the Creator for the better.